Sobre um critério de identidade de sentidos em Frege - Eduardo Antonio Pitt (2013)
In this thesis we will give primary attention to intensional notions present in formal language of Frege because we intend to delimit the discussion of problems related to the notion of identity of senses. In this way, I intend to show that in the theory of Frege the formulation of a logical criterion objective for identity of the senses was always problematic. We will look at: (i) the criteria of identity of conceptual content present in §§ 3 and 8 of Begriffsschrift and the semantic problems generated by these criteria. Throughout the dissertation will make considerations about the relationships that we can establish between the Frege's criterion of identity of conceptual content of complete sentences and, subsequently, the logical criterion of sentences equipollents with the criteria intensional of essential equivalence and equivalence of synonymy of judgments of Kirkham; (ii) the changes that Frege did in his conceptual notation after 1891, but we will focus on the semantic distinction between signal, sense and reference because I will give emphasis to the intensional notion of meaning of complete sentences, and (iii) the criteria of identity of thoughts suggested by Frege in two Letters to Husserl and in A brief survey of my doctrines logical. I analyze the applicability of logical criterion of sentences equipollents of Frege in relation to the peculiarities of the language, in relation to the criterion of synonymy of Kirkham and in relation to cases of identity of thoughts compounds.